Children and Young People-Mental Health Safety Assessment Tool (CYP-MH SAT) study: Protocol for the development and psychometric evaluation of an assessment tool to identify immediate risk of self-harm and suicide in children and young people (10–19 years) in acute paediatric hospital settings. Issue 4 (12th April 2018) - Manning, Joseph C; Walker, Gemma M; Carter, Tim; Aubeeluck, Aimee; Witchell, Miranda; Coad, Jane
Abstract : Introduction: Currently, no standardised, evidence-based assessment tool for assessing immediate self-harm and suicide in acute paediatric inpatient settings exists. Aim: The aim of this study is to develop and test the psychometric properties of an assessment tool that identifies immediate risk of self-harm and suicide in children and young people (10–19 years) in acute paediatric hospital settings. Methods and analysis: Development phase: This phase involved a scoping review of the literature to identify and extract items from previously published suicide and self-harm risk assessment scales. Using a modified electronic Delphi approach, these items will then be rated according to their relevance for assessment of immediate suicide or self-harm risk by expert professionals. Inclusion of items will be determined by 65%–70% consensus between raters. Subsequently, a panel of expert members will convene to determine the face validity, appropriate phrasing, item order and response format for the finalised items. Psychometric testing phase: The finalised items will be tested for validity and reliability through a multicentre, psychometric evaluation. Psychometric testing will be undertaken to determine the following: internal consistency, inter-rater reliability, convergent, divergent validity and concurrent validity. Ethics and dissemination: Ethical approval was provided by the National Health Service East Midlands—Derby Research Ethics Committee (17/EM/0347) and full governance clearance received by the Health Research Authority and local participating sites. Findings from this study will be disseminated to professionals and the public via peer-reviewed journal publications, popular social media and conference presentations.